2001
DOI: 10.1097/00004647-200107000-00005
|View full text |Cite
|
Sign up to set email alerts
|

Hypoperfusion without Ischemia Surrounding Acute Intracerebral Hemorrhage

Abstract: A zone of hypoperfusion surrounding acute intracerebral hemorrhage (ICH) has been interpreted as regional ischemia. To determine if ischemia is present in the periclot area, the authors measured cerebral blood flow (CBF), cerebral metabolic rate of oxygen (CMRO2), and oxygen extraction fraction (OEF) with positron emission tomography (PET) in 19 patients 5 to 22 hours after hemorrhage onset. Periclot CBF, CMRO2, and OEF were determined in a 1-cm-wide area around the clot. In the 16 patients without midline shi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
200
1
9

Year Published

2004
2004
2013
2013

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 340 publications
(223 citation statements)
references
References 44 publications
13
200
1
9
Order By: Relevance
“…The mean decrease in CBF was more marked in the Zazulia study ( À 16.1 mL/100 g per minute) relative to our results ( À 2.6 mL/100 g per minute). 12 This difference may be secondary to the inclusion of larger hemorrhages in the PET study, as hematoma volume has previously been shown to be predictive of perihematoma hypoperfusion. 6 More importantly, both studies indicated that the decrease in CBF is not severe enough to result in metabolic changes associated with ischemia.…”
Section: Perihematoma Region Metabolismmentioning
confidence: 99%
See 1 more Smart Citation
“…The mean decrease in CBF was more marked in the Zazulia study ( À 16.1 mL/100 g per minute) relative to our results ( À 2.6 mL/100 g per minute). 12 This difference may be secondary to the inclusion of larger hemorrhages in the PET study, as hematoma volume has previously been shown to be predictive of perihematoma hypoperfusion. 6 More importantly, both studies indicated that the decrease in CBF is not severe enough to result in metabolic changes associated with ischemia.…”
Section: Perihematoma Region Metabolismmentioning
confidence: 99%
“…6,7,10 It has long been hypothesized that perihematoma oligemia results from vascular compression by the hemorrhage. 2,11 A positron emission tomographic (PET) study has indicated that the perihematoma region is hypometabolic, 12 but it remains unclear whether this finding reflect either or both severe hypoperfusion and reduced metabolic demands. Acute CBF changes, and any effect these may have on the local delivery of oxygen, are relevant to ongoing studies of blood pressure (BP) reduction, as such treatment has the potential to exacerbate hypoperfusion and precipitate ischemic damage.…”
Section: Introductionmentioning
confidence: 99%
“…Currently a controversial issue is whether ischemic events represent a primary cause of cell injury or only a secondary consequence of tissue damage (Bouma et al, 1991;Diringer et al, 2002). Clinical studies have reported that ischemic levels of flow are only observed in irreversibly damaged tissue (Diringer et al, 2002;Zazulia et al, 2001). In contrast, other studies in head injured patients have demonstrated histopathological changes consistent with hypoxic/ischemic insults (Graham and Adams, 1971;von Oettingen et al, 2002) and severe flow reductions early after TBI (Bouma et al, 1991;Marion et al, 1991;von Oettingen et al, 2002).…”
Section: Cellular Vulnerabilitymentioning
confidence: 99%
“…Controversy exists regarding the acute treatment of hypertension in ICH because of the possible expansion of what was once believed to be ischemic penumbra surrounding the hematoma. However, more recent positron emission tomographic evidence has shown that the area surrounding the hematoma is more likely to be due to metabolic suppression and not ischemia, and it is not affected by blood pressure reduction [65].…”
Section: Blood Pressurementioning
confidence: 99%
“…The edema related to ICH has been cited as a reason for neurological deterioration after the first 24 to 48 h from the onset of symptoms [70], and it has, to a lesser degree, also been implicated with deterioration as late as 3 weeks [65]. The edema has been demonstrated to be predominately vasogenic with a cytotoxic component.…”
Section: Secondary Processesmentioning
confidence: 99%